2020
DOI: 10.3390/ph13040078
|View full text |Cite
|
Sign up to set email alerts
|

Methanolic Extract of the Herb Ononis spinosa L. Is an Antifungal Agent with no Cytotoxicity to Primary Human Cells

Abstract: Ononis spinosa L. is a plant traditionally used as folk remedy. There are numerous studies regarding chemical constituents and health beneficial properties of Ononidis Radix. The following study was designed to investigate chemical composition and antifungal potential of the methanolic extract obtained from the O. spinosa L. herb. Chemical analyses regarding phenolic compounds of O. spinosa were performed by liquid chromatography with mass spectrometry (LC-DAD-ESI/MSn). Antifungal activity, antibiofilm propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
(42 reference statements)
0
26
0
Order By: Relevance
“…One of the crucial steps at the very beginning of the development of novel antifungals is to observe the effects that the investigated compounds might have on cultured mammalian cells [ 50 ]. A previous study showed that camphor influenced the proliferation of fetal lung fibroblasts MRC-5 with IC 50 11.0 mM [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the crucial steps at the very beginning of the development of novel antifungals is to observe the effects that the investigated compounds might have on cultured mammalian cells [ 50 ]. A previous study showed that camphor influenced the proliferation of fetal lung fibroblasts MRC-5 with IC 50 11.0 mM [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aerial parts of the plant were lyophilized and reduced to a fine powder. Plant material was successively extracted with methanol according to the procedure described previously [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cytotoxic effect of A . cerefolium methanolic extract on HGF-1 cells was determined as described by Stojkovic et al, [ 42 ]. The A172 cells were grown in high-glucose Dulbecco’s Modified Eagle Medium (DMEM) supplemented with 10% fetal bovine serum (FBS), 2 mM L-glutamine and 1% penicillin and streptomycin at 37 °C in 10% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations